MRI-based quantification of primary ossification centers in the lateral and basilar parts of the human fetal occipital bone - Qinyi Han; Nan Lin; Peng Su; Hui Zhao; Peng Zhao; Mimi Tian; Lianjie Cheng; Lianxiang Xiao; Xiangtao Lin (BMC Medical Imaging)
Abstract Background The ossification of the occipital bone begins in the basilar part and progresses anteriorly, which is vital for the normal development of both the cranial and facial skeleton. Abnormal ossification of the occipital bone is associated with congenital anomalies such as Chiari malformation and anencephaly. Despite this, morphometric data on the ossification centers of the occipital bone, particularly in the lateral and basilar parts, remain limited. Purpose The aim of this study was to provide a detailed morphometric analysis of the primary ossification centers in the lateral and basilar parts of the occipital bone in human fetuses using high-resolution magnetic resonance imaging (MRI). Methods A total of 40 human fetuses (24 males and 16 females) aged 17 to 42 weeks of gestation were included in the study. These specimens were collected from spontaneous miscarriages and preterm deliveries, with all ethical standards followed. High-resolution MRI imaging was performed using a Siemens Magnetom Prisma 3T MRI scanner. 3D volumetric data of the ossification centers in the lateral and basilar parts of the occipital bone were acquired and analyzed using 3D Slicer software. Linear, planar, and volumetric parameters, including 3D maximum diameter, projection surface area, and volume, were measured for both parts of the occipital bone. Statistical analysis was conducted using SPSS Statistics 23 software, with regression analyses to model growth dynamics. Results The analysis revealed that the ossification centers of both the lateral and basilar parts of the occipital bone exhibited proportional growth relative to gestational age, with significant correlations between age and the measured parameters. The mean 3D maximum diameters, projection surface areas, and volumes showed consistent growth patterns, with no significant differences based on sex or laterality. The developmental dynamics were best described by linear regression models, with high coefficients of determination (R² > 0.75) for all parameters. Conclusion This study provides normative morphometric data for the primary ossification centers of the lateral and basilar parts of the occipital bone in human fetuses, offering valuable insights into the normal growth patterns of these structures. The findings contribute to the understanding of cranial base development and provide a reference framework for the early detection of congenital cranial anomalies. The use of MRI in fetal imaging proves to be a reliable and non-invasive method for studying fetal skeletal development. Clinical trial number Not applicable.